1991
DOI: 10.1038/nbt0891-725
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Morphology of Protein Inclusion Bodies in Escherichia Coli

Abstract: We have studied the structure and characteristics of inclusion bodies formed by the enzyme beta-lactamase in the periplasmic space of Escherichia coli or in the cytoplasm, following expression of the protein without its signal sequence. Electron microscopy of highly purified protein aggregates using a novel sucrose gradient centrifugation procedure revealed striking morphological differences. Periplasmic inclusion bodies were essentially amorphous whereas the protein particles in the cytoplasm were highly regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(142 citation statements)
references
References 28 publications
1
140
1
Order By: Relevance
“…The overexpressed GehA polypeptide was produced as inclusion bodies which were absent from control cell extracts. The irregular shape of these inclusion bodies might support the possibility that GehA was located in the periplasm, as a previous report (Bowden et al, 1991) suggested that periplasmic inclusion bodies could be differentiated from those expressed in the cytoplasm by their irregular morphology. The formation of soluble recombinant proteins in the periplasm of E. coli is often favoured by incubation at low temperature (Schein & Noteborn, 1988;Hockney, 1994) or in the presence of non-metabolizable sugars such as sucrose (Bowden & Georgiou, 1988), and a combination of both of these incubation parameters resulted in a marked increase in the production of active lipase polypeptide.…”
Section: Cloning and Expression Of P Acnes Lipasementioning
confidence: 64%
“…The overexpressed GehA polypeptide was produced as inclusion bodies which were absent from control cell extracts. The irregular shape of these inclusion bodies might support the possibility that GehA was located in the periplasm, as a previous report (Bowden et al, 1991) suggested that periplasmic inclusion bodies could be differentiated from those expressed in the cytoplasm by their irregular morphology. The formation of soluble recombinant proteins in the periplasm of E. coli is often favoured by incubation at low temperature (Schein & Noteborn, 1988;Hockney, 1994) or in the presence of non-metabolizable sugars such as sucrose (Bowden & Georgiou, 1988), and a combination of both of these incubation parameters resulted in a marked increase in the production of active lipase polypeptide.…”
Section: Cloning and Expression Of P Acnes Lipasementioning
confidence: 64%
“…However, even though the conformation of the aggregated protein appears to be similar, the incluaion bodies exhibit marked differences in morphology, in their resistance to protease digestion, and in solubilization by denaturants (Bowden et al, 1991). In addition, we have found that the yield of enzymatically active @-lactamase upon GuHCl solubilization and renaturation of inclusion bodies is generally low, whereas under the same experimental conditions the purified protein can be refolded quantitatively (Valax and Georgiou, 1993).…”
Section: Introductionmentioning
confidence: 86%
“…The outcome of the in vivo folding process, i.e., whether a protein reaches its native state or forms aggregates, depends on the folding pathway, interactions with cellular components such as chaperonins, the rate of protein synthesis, and growth conditions. The formation of inclusion bodies is not necessarily undesirable and can actually offer great advantages for protein production and purification (Georgiou and Bowden, 1991). However, the recovery of active protein from inclusion bodies generally requires the complete solubilization of the aggregates under strong denaturing conditions, which usually lead to the complete unfolding of the protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified recombinant IBs appear as spherical, ellipsoidal, or cylindrical particles measuring between 0.5 and 1.8 mm, characterized by a smooth and porous surface [36,37]. TsnC IBs consisted of spherical particles (Fig.…”
Section: Tsnc Ibmentioning
confidence: 99%